Perception Towards Halal Awareness And Its Correlation With Halal Certification Among Muslims - A. Siti Mashitoh,; Norhayati Rafida Abdul Rahim; Alina Abdul Rahim (IDOSI Publications, 2024)
Non-Indexed Publication